Speech recognition via phonetically-featured syllables - King, Simon; Taylor, Paul; Frankel, Joe; Richmond, Korin (University of the Saarland, 2000)
We describe recent work on two new automatic speech recognition systems. The first part of this paper describes the components of a system based on phonological features (which we call Espresso-P) in which the values of these features are estimated from the speech signal before being used as the basis for recognition. In the second part of the paper, another system (which we call Espresso-A) is described in which articulatory parameters are used instead of phonological features and a linear dynamical system model is used to perform recognition from automatically estimated values of these articulatory parameters.